2006
DOI: 10.1111/j.1600-0420.2006.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve pH and PO2: the effects of carbonic anhydrase inhibition, and metabolic and respiratory acidosis

Abstract: ABSTRACT.Purpose: Earlier studies have demonstrated that carbonic anhydrase inhibitors (CAIs) increase optic nerve oxygen tension (ONPO 2 ) in pigs. We hypothesized that the mechanism of this effect was either a CO 2 increase or a pH decrease in tissue and blood. To test this hypothesis we investigated and compared how optic nerve pH (ONpH) and ONPO 2 are affected by: (1) carbonic anhydrase inhibition; (2) respiratory acidosis, and (3) metabolic acidosis. Methods: We measured ONpH with a glass pH electrode and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
(25 reference statements)
2
11
0
Order By: Relevance
“…However, this does not mean that oxygen extraction has increased; there is only a potential increase in oxygen delivery. Previous studies have found that the carbonic anhydrase inhibition produced by dorzolamide may increase optic nerve oxygen tension in animal models (Noergaard et al 2008;Pedersen et al 2006;Pedersen et al 2005;la Cour et al 2000;Stefa´nsson et al 1999) and pilot research suggests that this may also occur in humans (Siesky et al 2008). Our data suggest that increased retinal blood flow is the most likely rationale for these changes, but this requires further confirmation.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, this does not mean that oxygen extraction has increased; there is only a potential increase in oxygen delivery. Previous studies have found that the carbonic anhydrase inhibition produced by dorzolamide may increase optic nerve oxygen tension in animal models (Noergaard et al 2008;Pedersen et al 2006;Pedersen et al 2005;la Cour et al 2000;Stefa´nsson et al 1999) and pilot research suggests that this may also occur in humans (Siesky et al 2008). Our data suggest that increased retinal blood flow is the most likely rationale for these changes, but this requires further confirmation.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have found that the carbonic anhydrase inhibition produced by dorzolamide may increase optic nerve oxygen tension in animal models (Noergaard et al. 2008; Pedersen et al. 2006; Pedersen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Within recent years the use of pigs as an in vivo experimental model in ophthalmological posterior-segment research has increased (Garcia et al 2005;Kiilgaard et al 2005;Petropoulos et al 2005;Schmidt Laugesen et al 2005;Stefansson et al 2005;Tao et al 2005;Warfinge et al 2005;Iandiev et al 2006;Kwan et al 2006;Pedersen et al 2006;Salyer et al 2006). There are anatomical similarities between the human and the porcine eye, macroscopic as well as histological, making this animal a good model when testing ophthalmologic treatment modalities and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Although causal relationships were not established between CA enzyme activity, venous blood variables, and GBD, the results did demonstrate associations between lower CA activity in the lens, abnormal gas production, and decreased pH in the venous blood of fish that were exposed to DGS. These results are supported by the work of Pedersen et al (2006), who observed a close correlation between blood pH and intraocular pH. Kinsey and Reddy (1959) produced important additional findings: that gaseous CO 2 was converted to the ion form in the ciliary epithelium with a half-life of less than 1 min and that the rate of HCO − 3 formation in aqueous humor was greatly slowed by inhibition of CA.…”
Section: Variablementioning
confidence: 66%